Cryptococcus neoformans requires the TVF1 gene for thermotolerance and virulence - Ueno, Keigo; Nagamori, Akiko; Honkyu, Nahoko Oniyama; Kataoka, Michiyo; Shimizu, Kiminori; Chang, Yun C; Kwon-Chung, Kyung J; Miyazaki, Yoshitsugu (Medical mycology (Oxford), 2023)
Cryptococcus neoformans is the primary causative agent of cryptococcosis. Since C. neoformans thrives in environments and its optimal growth temperature is 25-30°C, it needs to adapt to heat stress in order to cause infection in mammalian hosts. In this study, we aimed to investigate the role of an uncharacterized gene, CNAG_03308. Although the CNAG_03308 deletion strain grew as well as the parent strain KN99, it produced yeast cells with abnormal morphology at 37°C and failed to propagate at 39°C. Furthermore, the deletion strain exhibited slower growth at 37°C in the presence of congo red, which is a cell wall stressor. When cultured at 39°C, the deletion strain showed strong staining with fluorescent probes for cell wall chitin and chitosan, including FITC-labeled wheat germ agglutinin, Eosin Y, and calcofluor white. The transmission electron microscopy of the deletion strain revealed a thickened inner layer of the cell wall containing chitin and chitosan under heat stress. This cell-surface altered deletion strain induced dendritic cells to secrete more interleukin (IL)-6 and IL-23 than the control strains under heat stress. In a murine infection study, C57BL/6 mice infected with the deletion strain exhibited lower mortality and lower fungal burden in the lungs and brain compared to those infected with the control strains. Based on these findings, we concluded that CNAG_03308 gene is necessary for C. neoformans to adapt to heat stress both in vitro and in the host environment. Therefore, we designated the CNAG_03308 gene as TVF1, which stands for thermotolerance and virulence-related factor 1.